2016
DOI: 10.1093/ije/dyw128
|View full text |Cite
|
Sign up to set email alerts
|

Lung and stomach cancer associations with groundwater radon in North Carolina, USA

Abstract: Our study provides epidemiological evidence of a positive association between groundwater radon exposure and lung cancer incidence rates. The cluster membership model results find groundwater radon increases the odds that both lung and stomach cancer cases occur within their respective cancer clusters. The results corroborate previous biokinetic and mortality studies that groundwater radon is associated with increased risk for lung and stomach cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…The WHO report of 2009 [ 26 ], as well as other reports [ 27 , 28 ], did not discount possible effects of radon on cancers other than lung cancer. Radon has been examined in several studies of non-lung cancers, including esophageal cancer [ 29 ], stomach cancer [ 27 , 30 ] and leukemia [e.g., 28 , 31–33 ]. A large case-control study of radon and childhood leukemia in Denmark found a significant association that was not confirmed in population-based studies in Switzerland and Norway [ 34–36 ].…”
mentioning
confidence: 99%
“…The WHO report of 2009 [ 26 ], as well as other reports [ 27 , 28 ], did not discount possible effects of radon on cancers other than lung cancer. Radon has been examined in several studies of non-lung cancers, including esophageal cancer [ 29 ], stomach cancer [ 27 , 30 ] and leukemia [e.g., 28 , 31–33 ]. A large case-control study of radon and childhood leukemia in Denmark found a significant association that was not confirmed in population-based studies in Switzerland and Norway [ 34–36 ].…”
mentioning
confidence: 99%
“…However, neither factor was directly related to CRC rates. Although radon in groundwater has been associated with lung and with stomach cancer, to our knowledge, there is little evidence for an association between radon and CRC [19].…”
Section: Discussionmentioning
confidence: 90%
“…In a retrospective analysis that compared Rn levels for each county in Pennsylvania to the incidence and mortality of gastrointestinal cancer, a positive correlation was found for stomach cancer in females, and the mortality of stomach cancer for male, female, and total population [ 88 ]. Messier et al provided epidemiological evidence of a positive association between groundwater Rn concentration and an increase in the probability of a stomach cancer [ 87 ]. Moreover, Lopez-Abente evaluated the cancer mortality in Galicia and residential Rn levels.…”
Section: Resultsmentioning
confidence: 99%